Diskursus Kebijakan Sosial Membangun Keberlanjutan Kesejahteraan Petani di Berbagai Negara - Wulandary, Roro Merry Chornelia; Novianto Putra, Ronny Ersya (Lenvari: Journal of Social Science, 2024)
The main objective of this systematic review article is to determine the implementation of social protection to maintain the sustainability of farmers' welfare, especially organic farming. The author answers the research question about How to implement sustainable social protection to realize the welfare of organic farmers in various countries? The researcher first describes the scientific view (Definition of organic farming and factors of organic farming); social policy indicators (state protection, accessibility of easy and affordable farming businesses, utilization of social capital, encouragement of organic certification for small farmers, market sustainability); and policy output (economic and social sustainability